Dopaminergic Stimulation of Myeloid Antigen-Presenting Cells Attenuates Signal Transducer and Activator of Transcription 3-Activation Favouring the Development of Experimental Autoimmune Encephalomyelitis - Prado, Carolina; Gaiazzi, Michela; González, Hugo; Ugalde, Valentina; Figueroa, Alicia; Osorio-Barrios, Francisco J.; López, Ernesto; Lladser, Alvaro; Rasini, Emanuela; Marino, Franca; Zaffaroni, Mauro; Cosentino, Marco; et al. (Frontiers in Immunology, 2018)
The dual potential to promote tolerance or inflammation to self-antigens makes dendritic cells (DCs) fundamental players in autoimmunity. Previous results have shown that stimulation of dopamine receptor D5 (DRD5) in DCs potentiates their inflammatory behaviour, favouring the development of experimental autoimmune encephalomyelitis (EAE). Here we aimed to decipher the underlying mechanism and to test its relevance in multiple sclerosis (MS) patients. Our data shows that DRD5-deficiency confined to DCs in EAE mice resulted in reduced frequencies of CD4+ T-cell subsets with inflammatory potential in the central nervous system, including not only Th1 and Th17 cells, but also GM-CSF producers. Importantly, ex vivo depletion of dopamine from DCs resulted in a dramatic reduction of EAE severity, highlighting the relevance of an autocrine loop promoting inflammation in vivo. Mechanistic analyses indicated that DRD5-signalling in both mouse DCs and human monocytes involves the attenuation of STAT3-activation, a transcription factor that limits the production of the inflammatory cytokines IL-12 and IL-23. Furthermore, we found an exacerbated expression of all dopamine receptors in peripheral blood pro-inflammatory monocytes obtained from MS patients. These findings illustrate a novel mechanism by which myeloid antigen-presenting cells may trigger the onset of their inflammatory behaviour promoting the development of autoimmunity.